Integration of the Authorities of APIP and BPK in Calculating State Financial Losses - Murad Fadirah; Moh Fadli; Shinta Hadiyantina (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2026)
This study aims to analyze the legal implications of the differences in the positions and sources of authority of the APIP and the BPK in calculating state losses against the evidentiary value of audit results in corruption cases, as well as to analyze the integration model of the APIP and BPK authorities to avoid potential differences in audit results in determining the amount of state financial losses. The research method used is normative juridical legal research. The approaches used are the statute approach, the conceptual approach, and the case approach. The results of this study indicate that the positions and sources of authority of the APIP and the BPK have implications for the evidentiary strength of audit results in corruption cases. The integration of authority between the APIP and the BPK can be done through a single gate authority mechanism that positions the BPK as the supreme audit institution that must be coordinated by law enforcement officials to avoid differences in audit results in calculating state losses.